Sodium chloride stimulates the biomass and astaxanthin production by Haematococcus pluvialis via a two-stage cultivation strategy. (January 2022) - Li, Qingqing; You, Jinkun; Qiao, Tengsheng; Zhong, Du-bo; Yu, Xuya
Graphical abstract: Highlights: A two-stage strategy using NaCl for algal biomass and astaxanthin yield was proposed. Low-dose NaCl induced algal growth, while the high-dose facilitated astaxanthin synthesis. Sophisticated crosstalk occurred among ROS, GABA and Ca 2+ in astaxanthin accumulation. Abstract: A major challenge facing by astaxanthin industrialization is the low productivity and high production costs. This study established a two-stage cultivation strategy based on the application of NaCl to improve the production of biomass and astaxanthin by Haematococcus pluvialis. During the first growth stage, 12.5 mg L -1 NaCl led to a remarkable enhancement in biomass, which was 1.28 times compared with the control. Moreover, 2 g L -1 NaCl stimulated the astaxanthin content from 12.18 mg g −1 to 25.92 mg g −1 during the second induction stage. Simultaneously, salinity stress application increased the lipids and GABA contents, as well as the levels of Ca 2+ and carotenogenic genes' expression, but suppressed the contents of carbohydrate and protein and high-light induced-ROS. This study proposed a simple and convenient strategy for efficient coproduction of biomass and astaxanthin and provides insights into the underlying mechanism of astaxanthin biosynthesis in H. pluvialis induced by salinity stress.